P-119 Re-establishing hospice day services with user involvement. (19th November 2022) - Bagan, Christine; Hutton, Paul; Storrar, Jemma; Whyle, Lucy
Abstract : Background: Hospice day services enable those living with a life-limiting illness to access a range of services within a safe environment while at the same time providing respite and support to their family caregivers. We recognised the need for a more therapeutic service model and set about developing a new proposal, incorporating user involvement to improve the quality of the service. Aim: To develop and implement a new day service proposal, providing a more therapeutic environment which gives the patient an increased sense of confidence and empowerment to support them in living with their illness as well as providing support to carers. Methods: In July 2021 a working group was established to generate thoughts on our new day service. A survey was also sent to patients and carers to establish their wishes and our local Hospice User Group was asked to contribute. Results: The working group came up with a 5-day service offering a person-centred day service programme comprising a range of group sessions and physical well-being classes. User Feedback = Top 5 service needs - complementary therapy (92%); long term condition clinics (84%); listening support (77%), counselling (62%); coffee mornings (62%); health and wellbeing services (62%). Other suggestions included a Progressive Supranuclear Palsy clinic, specific support for an illness, keep fit classes and various workshops i.e., how to deal with loss, what to expect before death. Conclusion: A re-evaluation of hospice day services involving staff and users has enabled us to develop a comprehensive day service proposal which we are now in the process of implementing. Progress to date includes an increased complementary therapy service, the establishment of a carer support group, and more recently a weekly coffee and cake morning. The implementation plan is still underway, and we aim to have our new hospice day service - 'The Hive' - fully up and running within three months.